Nephrotoxicity after ifosfamide. Issue 7 (July 1990) - Skinner, R; Pearson, A D; Price, L; Coulthard, M G; Craft, A W
Abstract : Eleven children and adolescents with previously normal renal function who received ifosfamide for the treatment of extrarenal solid tumours underwent detailed investigation of glomerular and renal tubular function to assess the incidence and extent of renal damage. None had received cisplatin. Glomerular filtration rate (measured by plasma clearance of 51Cr labelled edetic acid) was reduced in six children. All 11 patients had evidence of proximal, and six of distal, tubular damage. Proximal tubular toxicity was indicated by phosphaturia and hypophosphataemia (n = 4), glycosuria (n = 5), increased urine beta 2 microglobulin excretion (n = 11), and generalised aminoaciduria (n = 10); distal tubular damage caused a reduction of the osmolality of the urine in an early morning sample. Two children developed clinical hypophosphataemic rickets, and one of these also had severe nephrogenic diabetes insipidus. Glomerular and tubular nephrotoxicity are common and potentially serious complications of ifosfamide treatment in children.